Echogenic intracardiac focus on second trimester ultrasound: prevalence and significance in a Middle Eastern population. (17th July 2016) - Mirza, Fadi G.; Ghulmiyyah, Labib; Tamim, Hani; Bou Hamdan, Farah; Breidy, Juliana; Geagea, Sandra; Usta, Ihab; Adra, Abdallah; Nassar, Anwar H.
Abstract: Objective : The association between echogenic intracardiac focus (EIF) and trisomy 21 is well established, with a recognized ethnic variation. Our study aimed to determine the prevalence of EIF in a Middle Eastern population and to examine its association with trisomy 21 and other adverse pregnancy outcomes. Methods : Retrospective case-control study of second-trimester obstetric sonograms (16–28 weeks) performed at a tertiary care center over a 5-year period. Cases with EIF were retrieved, and a matched control group with no EIF was identified. The incidence of trisomy 21 and other adverse pregnancy outcomes was compared. Results : A total of 9270 obstetric sonograms were examined, with an EIF prevalence of 2.5% (95% CI: 2.2–2.8%). Of patients with available outcome data, EIF was not associated with trisomy 21 (0/163 versus 1/163; p value = 1.00). Additionally, EIF was not associated with trisomy 18, trisomy 13, small for gestational age, preterm birth, fetal demise, cesarean delivery, operative vaginal delivery, or admission to the neonatal intensive care unit. Conclusion : In a contemporary Middle Eastern population, EIF is a rare occurrence. As an isolated finding, it is not associated with aneuploidy or other adverse pregnancy outcomes. EIF appears to be incidental with no impact on clinical practice.